Konsensus Kemitraan Global PBB (MDGs & SDGs), Hipotesis Environmental Kuznet Curve (EKC), dan Degradasi Kualitas Udara di Indonesia Periode 1980-2018 - Yoga Putra Pratama (Universitas Diponegoro, 2020)
The commitment of countries all over the world to overcome the air quality degradation was agreed upon United Nations Global Networking Consensus of Millenium Development Goals (for 2000-2015) and Sustainable Development Goals (for 2015-2030). The aims of this research were to investigate the impact of Indonesian commitment of United Nations Global Networking Consensus towards the air quality degradation and to prove the existence of U-inverted curve hypothesis (Environmental Kuznet Curve) from 1980 -2018 in Indonesia using the estimation technique of Error Correction Model (ECM) Engelman-Granger in order to reveal the short-term and Ordinary Least Square regression in order to reveal the long-term relationship. The impact of Global Networking Consensus of United Nations that agreed upon the Indonesian Government explained by the using of dummy variable with the aim of distinguish the year before and after this consensus implemented in Indonesia. This research was conduct within 2 models, which had 2 different dependent variables, which are CO2 emission per capita and CO2 emission in total. The result of the study showed that EKC is proved long term, but was not proved in short term when CO2 emission per capita was being the dependent variable,, with the reason of Indonesia is still a developing country which was prioritizes the increasing of income per capita without considering the environmental degradation, but someday Indonesia will pass the turning point and increase the income per capita while the environmental degradation is decrease at once. The dummy variable was significant in short term but not significant in long term since Indonesia is not a country that obliged to reduce CO2 emissions but has an interest to participate in reducing CO2 emissions based on the MDGs and SDGs agreement. The population growth has a significant positive effect and energy consumption per capita has positive sign and significant.